2022
DOI: 10.3389/fphys.2022.838450
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cardiorespiratory Fitness on Cerebral Oxygenation in Healthy Adults: A Systematic Review

Abstract: IntroductionExercise is known to improve cognitive functioning and the cardiorespiratory hypothesis suggests that this is due to the relationship between cardiorespiratory fitness (CRF) level and cerebral oxygenation. The purpose of this systematic review is to consolidate findings from functional near-infrared spectroscopy (fNIRS) studies that examined the effect of CRF level on cerebral oxygenation during exercise and cognitive tasks.MethodsMedline, Embase, SPORTDiscus, and Web of Science were systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 84 publications
(205 reference statements)
0
9
0
Order By: Relevance
“…For example, increased blood flow to brain structures such as the hippocampus, may be beneficial, as these brain regions comprise limbic pathways related to psychological distress and stress regulation (Aghjayan et al, 2021; Firth et al, 2018; Malykhin et al, 2010). Another mechanism may be the cognitive improvement associated with increasing blood flow in the prefrontal cortex (Salzman et al, 2022; Tavares et al, 2021), due to its important role in the regulation of rewards, emotions, and self-control (Kelley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased blood flow to brain structures such as the hippocampus, may be beneficial, as these brain regions comprise limbic pathways related to psychological distress and stress regulation (Aghjayan et al, 2021; Firth et al, 2018; Malykhin et al, 2010). Another mechanism may be the cognitive improvement associated with increasing blood flow in the prefrontal cortex (Salzman et al, 2022; Tavares et al, 2021), due to its important role in the regulation of rewards, emotions, and self-control (Kelley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This study has many limitations, which may account for the differences between our results and most previous studies. First, previous studies have found that individuals with higher VO2 peak and VO 2max and more physically active participants may show better executive function in a single task ( Goenarjo et al, 2020a ; Goenarjo et al, 2020b ; Goenarjo et al, 2021 ; Salzman et al, 2022 ). However, no such differences were found when evaluated using the estimated VO 2max .…”
Section: Discussionmentioning
confidence: 99%
“…The sports types in previous research were primarily strategic sports ( 31 , 32 ), and the activation of right IFG was found by controlling the exercise intensity to moderate intensity. Studies have shown that brain activation in the elderly was affected by exercise intensity, with higher exercise intensities (higher VO 2max ) more likely to contribute to increased cerebral oxygenation in the elderly ( 60 , 61 ). In contrast, the Baduanjin exercise used in the present study was a closed-loop exercise with low intensity, which may lead to a non-significant activation effect after the intervention.…”
Section: Discussionmentioning
confidence: 99%